Increasing exposure of cotton growing areas to compound drought and heat events in a warming climate - Shengli Liu; Wei Zhang; Tongtong Shi; Tong Li; Hui Li; Guanyin Zhou; Zhanbiao Wang; Xiongfeng Ma (Agricultural Water Management)
Cotton (Gossypium hirsutum L.) is a critical source of natural fiber and cottonseed oil for humans, yielding substantial economic benefits globally. However, the susceptibility of cotton cultivation to compound drought and heat events (CDHEs) brings significant threats to cotton productivity. Despite this, a comprehensive assessment of global CDHE occurrence over cotton-growing areas and its potential impacts on cotton yields remains unresolved, hindering efforts to implement adaptive strategies to ensure global cotton productivity. To address this gap, we analyzed changes in mean temperature and soil moisture within global cotton-growing areas during their respective growing seasons, estimated the probability of CDHEs across multiple spatial scales via copula theorems, and examined the relationship between cotton yield anomalies and CDHEs in major cotton countries. Our results indicate increasing but divergent trends in mean temperature and soil moisture. Specifically, while most regions exhibit drying trends, India and Pakistan show significant wetting trends, with soil moisture increasing during the cotton growing season. The global average probability of CDHEs between 1961–1990 and 1991–2020 showed a more than threefold increase in severity, with such an increase occurring in approximately 61 % of cotton-growing areas due to comparable contributions from drying and warming trends. Furthermore, major cotton-producing countries exhibited similar CDHE trends, leading to a heightened probability of synchronous CDHE occurrences, except in countries connected to India and Pakistan. Such occurrences of CDHEs are significantly related to cotton yield failures in major cotton-producing countries. Our findings emphasize the growing exposures of cotton-growing areas to CDHEs and highlight the urgent need for adaptive strategies to enhance the resilience of cotton production systems under changing climatic conditions.